ANALISIS IMPLEMENTASI STRATEGI PROMOSI DALAM MENGHADAPI PERSAINGAN (KASUS PADA AJB BUMIPUTERA 1912 WILAYAH PEKANBARU) - Arjuna, Wahyu Satria; Zuliarni, Sri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The problem in this study is still a lack of advertising and sales promotion undertaken and in the last five years, only in 2011 the realization of achieving the target number of customers that have been set can be achieved. In addition to a decrease in the achievement of the target customers in 2012 compared to 2011. The purpose of the study was to analyze the implementation of promotional strategies implemented by AJB Bumiputera 1912 Pekanbaru region in the face of competition. The results of the overall study respondents regarding the implementation of promotional strategies on AJB Bumiputera 1912 Regional Pekanbaru. Overall the respondents to the implementation of the promotion of good enough. However for advertising and sales promotion indicator is still not good. Not good indicators of advertising because the ads from insurance products AJB Bumiputera 1912 Pekanbaru region is still lacking and only limited to the offices of AJB Bumiputera 1912 alone. Besides advertising done only in the form of brochures, banners and flags in the office, so the scope is very limited. As for sales promotion, it is still very rare and almost never even AJB Bumiputera 1912 Regional Pekanbaru sales promotion by organizing exhibitions in the center of the crowd as well as to sponsor entertainment events. Entertainment events conducted only from the company itself as well as launching new products the company birthday celebration. Promotion is concerned with private sale (personal selling) is carried out through an agent.Keywords: advertising, sales promotion, personal selling, publicity